MELATIH KREATIAVITASANAK DI DUSUN BANDUNG DAN DUSUNSONGBANYU 1,KECAMATAN GIRI SUBO, GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA,MELALUI PEMBUATAN KOTAK PENSIL BERBAHAN DASAR KERTAS DAN KARTON - Muntoha Muntoha (UII, 2015)
Creativity is generating things activities that are new or innovative, useful orbeneficial, and can be understood or easily understood. Creative thinking is very importantfor a person, especially for children whose their brains are at the time of maximumdevelopment. Unfortunately, world development that is too fast make most people haveof consumer behavior and practicality lover, as occurs to children in Dusun Bandung andDusun Songbanyu 1, Kecamatan Giri Subo, Gunung Kidul, Daerah Istimewa Yoyakarta. Toreduce these behaviors, authors was initiated a simple training to make a pencil casethatis made from paperboard and origami paper. With hope, the children become morecreative and better able to take advantage of items that are around them.